1997
DOI: 10.1046/j.1365-3180.1997.d01-73.x
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation of imazapyr, flumetsulam and thifensulfuron in soil

Abstract: The degradation of imazapyr, fiumetsulam and thifensulfuron applied at 500, 40 and . M) g active ingredient (a.i,) ha"', respectively, to si!t loam soil was sttidied under laboratory and field conditions. Herbicide residues were analysed by a lentil {Lem culinaris L.) bioassay. Results showed ihat temperature had a significant effect on herbicide degradation. Vk'hereas the impact of soil organic matter ami pH were less well defined. Half-lives for iniazapyr, flumetsulam and thifensulfuron in soil samples from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0
5

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 7 publications
4
16
0
5
Order By: Relevance
“…No entanto, outro aspecto importante a ser considerado é que, em solo arenoso e com invernos chuvosos, pode haver maior lixiviação dos herbicidas, levando assim a resultados diferentes do encontrado neste experimento, podendo os herbicidas ser transportados para profundidades maiores no solo, ficando fora da região de absorção das plantas (McDowell et al, 1997;Jourdan et al, 1998).…”
Section: Resultsunclassified
“…No entanto, outro aspecto importante a ser considerado é que, em solo arenoso e com invernos chuvosos, pode haver maior lixiviação dos herbicidas, levando assim a resultados diferentes do encontrado neste experimento, podendo os herbicidas ser transportados para profundidades maiores no solo, ficando fora da região de absorção das plantas (McDowell et al, 1997;Jourdan et al, 1998).…”
Section: Resultsunclassified
“…Concordando com isso, McDowell et al (1997) eHJourdan et al (1998 -1 ), semeada após um ano da última aplicação dos herbicidas, num sistema com dois anos de uso dos herbicidas, em cinco épocas de avaliação e nove preparos de solo: PD = plantio direto; PDA = plantio direto mais azevém; 1PSA = um preparo de solo (PS), em abril; 1PSAA = um PS em abril mais azevém; 1PSO = um PS, em outubro; 2PSMO = dois PS, em maio e outubro; 2PS = dois PS, em abril e outubro; 3PS = três PS, em abril, maio e outubro; 4PS = quatro PS, em abril, maio, agosto e outubro. Santa Maria-RS, 2006/07.…”
Section: Resultsunclassified
“…10,11) Organic matter and pH significantly affect imazethapyr behavior in soil. 8,12) However, imazethapyr does not readily leach under field conditions, 13) even though some authors have reported leaching of imazethapyr below 25 cm in soil during four months. 8,14) As a result of leaching and runoff, imazethapyr residues were reported in streams and rivers in the Midwestern USA at concentrations above the maximum residue limits in 71% of samples.…”
Section: Introductionmentioning
confidence: 99%